Meningkatkan Keterampilan Membaca Nyaring Peserta didik Menggunakan Metode Suku Kata Berbantuan Media Kartu Bergambar - Sitti Nur Fadillah; Sisriawan Lapasere; Muhammad Aqil; Kadek Hariana; Ryan Andika Pratama; Vera Angelina Pesik (Jurnal Elementaria Edukasia, 2024)
This research aimed to determine the improvement of oral reading skills by practising the syllable-assisted visual aid method using picture cards among first grade students at SD Negeri 24 Palu, Palu City, Central Sulawesi. The research was conducted in SD Negeri 24 Palu with 28 first grade students. Data collection methods included observation, testing and documentation, while data analysis used a descriptive quantitative and qualitative approach. This research is a type of classroom action research that consists of four phases: planning, implementation, observation and evaluation. The results of the data analysis show that in the first test only 50% of the students achieved classical completeness or scored above the minimum criteria. However, in cycle 1, the percentage of students achieving classical completeness increased to 85%. These results indicate a significant improvement in students' oral reading skills with the use of the syllable method supported by visual aids in the form of picture cards